Adding Chinese Herbal Medicine to Routine Care is Associated With a Lower Risk of Rheumatoid Arthritis Among Patients With Asthma: A Population-Based Retrospective Cohort Study - Chang, Wei-Chiao; Livneh, Hanoch; Chen, Wei-Jen; Hsieh, Chang-Cheng; Wang, Yu-Han; Lu, Ming-Chi; Guo, How-Ran; Tsai, Tzung-Yi (Frontiers in Pharmacology, 2022)
Objective: Due to the shared pathogenesis of asthma and rheumatoid arthritis (RA), patients with asthma were found to have a higher risk of RA. While the benefits and safety of Chinese herbal medicine (CHM) for asthma have been reported, the scientific evidence regarding its effect on RA is limited. This longitudinal cohort study aimed to determine the relation between CHM use and RA risk in patients with asthma. Methods: Using the nationwide claims data, we enrolled 33,963 patients 20-80 years of age who were newly diagnosed with asthma and simultaneously free of RA between 2000 and 2007. From this sample, we utilized propensity score matching to create sets of participants as treatment and control groups, which comprised 13,440 CHM users and 13,440 non-CHM users. The incidence rate and hazard ratio (HR) for RA between the two groups was estimated at the end of 2013. A Cox proportional hazards model was constructed to examine the impact of the CHM use on the risk of RA. Results: The cumulative incidence of RA was substantially lower in the CHM user group. In the follow-up period, 214 patients in the CHM user group (1.92 per 1000 person-years) and 359 patients in the non-CHM user group (2.92 per 1000 person-years) developed RA (adjusted HR = 0.63, 95% confidence interval: 0.54–0.75). Of the commonly-prescribed formulae, nine CHM products were associated with a lower RA risk: Xiao-Qing-Long-Tang, Ma-Xing-Gan-Shi-Tang, Ding-Chuan-Tang, Xin-Yi-Qing-Fei-Tang, Bei Mu, Jie Geng, Xing Ren, Da Huang, and San Chi. Conclusion: This study found that patients with asthma who received CHM treatment, in addition to the conventional therapy, had a lower risk of RA. Use of CHM treatment may be integrated into conventional therapy to reduce subsequent RA risk among asthma patients.